The Dark Tetrad Personality Traits of Tax Avoidance in the Manufacturing Small and Medium Enterprises; an Empirical Evidence from Indonesia - Girindratama, Muhammad Wisnu Girindratama; Nuswantara, Dian Anita; Alnajar, Ali Elazumi Ali (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2024)
Introduction/Main Objectives: This study is to examine the tetrad personality traits (Narcissism, Psychopathy, Machiavellianism and Sadism) on tax avoidance in Indonesian small and medium enterprises (SMEs). In this study, we enter the role of rationalization as an intervening variable. Background Problems: Previous studies have extensively delved into the examination of firm characteristics and corporate governance as potential predictors of tax avoidance. One notable limitation in the existing body of research is the insufficient attention paid to the individual traits of financial preparers within firms. The personality traits and ethical orientations of these preparers can play a pivotal role in shaping the tax strategies adopted by companies. Overlooking the role of individual traits in tax-related decision-making may result in an incomplete understanding of the dynamics influencing tax avoidance behaviors. Novelty: This study is the first of its kind to examine the tetrad personality traits on tax avoidance by rationalization as an intervening variable. Research Methods: This research distribute questionnaires to the financial department in the Indonesian small and medium enterprises, particularly those are located in east java. The final data analyzed in this study are 284 questionnaires. Findings/Results: The results of this comprehensive study provide compelling evidence supporting the notion that firms led by individuals possessing the Tetrad Personality Traits—Narcissism, Psychopathy, Machiavellianism, and Sadism—are more prone to endorsing and actively engaging in tax avoidance practices by justifying tax avoidance as a tolerable action. Conclusion: The evidence presented in this research establishes a compelling link between the psychological characteristics of key decision-makers and the organizational behavior of justifying tax avoidance as an acceptable course of action. The theoretical and practical implications are discussed in this paper.